Inhuman land searching for the truth in Soviet Russia, 1941-1942 - Czapski, Józef 1896-1993 (New York Review Books, 2018)
"In 1941, when Germany turned against the USSR, tens of thousands of Poles...men, women, and children who were starving, sickly, and impoverished...were released from Soviet prison camps and allowed to join the Polish army being formed in the south of Russia. One of the survivors who made the difficult winter journey was the painter and reserve officer Józef Czapski. General Anders, the army's commander in chief, assigned Czapski the task of receiving the Poles arriving for military training; gathering accounts of what their fates had been; organizing education, culture, and news for the soldiers; and, most important, investigating the disappearance of thousands of missing Polish officers. Blocked at every level by the Soviet authorities, Czapski was unaware that in April 1940 the officers had been shot dead in Katyn forest, a crime for which Soviet Russia never accepted responsibility. Czapski's account of the years following his release from the camp, the formation of the Polish army, and its arduous trek through Central Asia and the Middle East to fight on the Italian front is rich in anecdotes about the suffering of the Poles in the USSR, quotations from the Polish poetry that sustained him and his companions, encounters with literary figures (including Anna Akhmatova), and philosophical thoughts about the relationships between nationalities"...
Translation of: Na nieludzkiej ziemi. - Includes bibliographical references
Keywords: Czapski, Józef -- 1896-1993; Sowjetunion -- Raboče-Krestʹjanskaja Krasnaja Armija -- Armija Andersa; Kriegsgefangenenlager Starobelsk; Geschichte 1941-1942; Geschichte; Autobiographies / lcgft; World War, 1939-1945 -- Prisoners and prisons, Russian; World War, 1939-1945 -- Personal narratives, Polish; Prisoners of war -- Poland -- Biography; Prisoners of war -- Soviet Union -- Biography; Soldat; Zweiter Weltkrieg; Straflager; Polen; Erlebnisbericht